Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1093/pasj/52.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Galactic Black-Hole Candidates Shining at the Eddington Luminosity

Abstract: We discuss distinctive features of luminous accretion disks shining at the Eddington luminosity in the context of galactic black-hole candidates (GBCs). We first note that the standard-disk picture is not applicable, although it is often postulated. Rather, the disk becomes advection-dominated while remaining optically thick (the so-called slim disk). The slim disk exhibits several noteworthy signatures: (1) The disk luminosity is insensitive to the mass-flow rates, Ṁ, and is always kept around the Eddington l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
331
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(360 citation statements)
references
References 1 publication
26
331
1
2
Order By: Relevance
“…Instead of the MCD model, the p-free disk model, expected from a onedimensional slim disk (Abramowicz et al 1988), gives a statistically acceptable fit to the spectrum in Epoch II . We consider it physically unlikely, however, because the inferred innermost radius is too small ( 0.3r g ) than a theoretical prediction (Watarai et al 2000). Also, we cannot consistently explain the spectra of two epochs with the same model.…”
Section: Origin Of X-ray Continuum Emission In "Soft State"mentioning
confidence: 72%
“…Instead of the MCD model, the p-free disk model, expected from a onedimensional slim disk (Abramowicz et al 1988), gives a statistically acceptable fit to the spectrum in Epoch II . We consider it physically unlikely, however, because the inferred innermost radius is too small ( 0.3r g ) than a theoretical prediction (Watarai et al 2000). Also, we cannot consistently explain the spectra of two epochs with the same model.…”
Section: Origin Of X-ray Continuum Emission In "Soft State"mentioning
confidence: 72%
“…With this value, a minimum distance of ∼36 km is acceptable, and considering the large uncertainty in the mass, which might be slightly overestimated, our results are not in conflict with the general scenario adopted for this peculiar source. On the other hand, the calculations of Watarai et al (2000) for the emission from a slim disk, demonstrated that radiation can be produced at distances much smaller than the last stable orbit, i.e. in the region between R S and 3R S .…”
Section: The Multi-temperature Disk Parametersmentioning
confidence: 99%
“…Fitting points from all segments, except for that containing the pulse, with a power-law, the resulting values for the temperature exponent are 2.7 ± 0.4 for SLT-1, 2.0 ± 0.5 for SLT-2, and 1.9 ± 0.2 for FDT, respectively. Several models have been proposed to explain the relation L ∝ T 2 for a slim disk where advection dominates the energy transfer in the inner region and reduces the radiation efficiency (Watarai et al 2000). Moreover, the effects of the large inclination angle cannot be neglected since deviations from the L ∝ T 4 relation are mainly observed in highly inclined sources (Done et al 2007).…”
Section: The Multi-temperature Disk Parametersmentioning
confidence: 99%
“…Although the scenario may be salvaged by invoking rapid BH rotation (Mizuno et al 1999;Paper I;also Zhang, Cui, & Chen 1997a) and/or a "slim disk" concept (Abramowicz et al 1988;Watarai et al 2000), it is important to assemble further observational clues.…”
mentioning
confidence: 99%